Role of Inducible Nitric Oxide Synthase in Resistance to Mycobacterium leprae in Mice - Adams, Linda B. (American Society for Microbiology, 2000)
The manifestation of leprosy in humans is largely determined by host immunity to Mycobacterium leprae and is a model for immunoregulation in a human disease. However, animal models available for exploration of the leprosy spectrum are inadequate. This study explored M. leprae infection in mice deficient in inducible nitric oxide synthase, and this report describes elements resembling borderline tuberculoid leprosy in humans.